Antibacterial activities of endophytic fungi isolated from six Sri Lankan plants of the family Cyperaceae - Ratnaweera, Pamoda B.; Walgama, R. Chandula; Jayasundera, Kinkini U.; Herath, Suseema D.; Abira, S.; Williams, David E.; Andersen, Raymond J.; de Silva, E. Dilip (Bangladesh Journal of Pharmacology, 2018)
In a study designed to determine the antibacterial potential of endophytic fungi inhabiting plants of Cyperaceae family, 72 morphologically distinct endophytic fungi were isolated from six plants and their antibacterial activities against two Gram positive and three Gram negative pathogenic bacterial species were examined. Two antibacterial metabolites from two endophytes were also isolated and their chemical structures and minimum inhibitory concentrations were determined. Sixty six fungal extracts (92%) were active against at least one bacterium tested. Butyrolactone I isolated from the Aspergillus terreus and 9-epi viridol isolated from Trichoderma virens exhibited MIC values in the range 128-256 µg/mL against Gram positive Bacillus subtilits, Staphylococcus aureus, methicillin resistant S. aureus (MRSA) and Escherichia coli. Both compounds were inactive against other micro-organisms tested. This study confirmed that Cyperaceae plants harbor numerous endophytes that produce antibacterial metabolites active against both Gram positive and, to a lesser extent, Gram negative bacteria. Video Clip of Methodology: Column Chromatogrpahy: 15 min 34 sec Click to watch